FAKTOR PENGARUH PEMILIHAN JARAK AKSES DARI TEMPAT TINGGAL MENUJU TEMPAT PEMBERHENTIAN BUS - Gultom, Hansen Samuel Arberto; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Public transport stops should be planned in such a way to attract more people to use it. The purpose of this study is to examine the influencing factors to the selection of travel distance from home to bus stop. The results show that majority of users of Trans Metro Bandung travelled less than 300 meters to reach bus stop. Aspects or variables that are discussed in this study are gender, age, marital status, status at the household, household conditions, occupation, monthly expenses, monthly travel expenses, mode to reach bus stops, and luggage. The results of the analysis using ordinal logit model show that the influencing aspects of the distance from home to the bus stops are gender and mode to reach bus stops.